Trabecular Bone Microarchitecture Improvement Is Associated With Skeletal Nerve Increase Following Aerobic Exercise Training in Middle-Aged Mice - Lee, Seungyong; Shin, Yun-A; Cho, Jinkyung; Park, Dong-ho; Kim, Changsun (Frontiers in Physiology, 2022)
Advancing age is associated with bone loss and an increased risk of osteoporosis. Exercise training may play a critical role in osteogenesis and increase in skeletal nerve fiber density in aging. The potential positive role of aerobic exercise training in bone metabolism and skeletal nerve regeneration was comprehensively evaluated in 14-month-old male C57BL/6 mice. The mice were divided into two groups: no exercise (non-exercise) and 8-weeks of aerobic exercise training (exercise). Dual-energy X-ray absorptiometry and micro-computed tomography showed that femoral and tibial bone parameters improved after aerobic exercise training. Greater skeletal nerve fiber density was also observed in the distal femoral and proximal tibial periostea, measured and analyzed by immunofluorescence staining and confocal microscopy. Pearson correlation analysis revealed a significant association between skeletal nerve densities and trabecular bone volume/total volume ratios (distal femur; R2 = 0.82, p < 0.05, proximal tibia; R2 = 0.59, p = 0.07) in the exercise group; while in the non-exercise group no significant correlation was found. Analysis of archival microarray database confirmed that aerobic exercise training changed the microRNA profiles in the mice femora. The differentially expressed microRNAs reinforce the role of aerobic exercise training in the osteogenic and neurogenic potential of femora and tibiae. In conclusion, 8-weeks of aerobic exercise training positively regulates bone metabolism, an effect that paralleled a significant increase in skeletal nerve fiber density. These findings suggest that aerobic exercise training may have dual utility, both as a direct stimulator of bone remodeling and a positive regulator of skeletal nerve regeneration.